Does Combination Therapy with Desmopressin and Tolterodine Improve the Treatment Outcomes of Patients with Monosymptomatic Nocturnal Enuresis? A Randomized Clinical Controlled Trial. (25th March 2013) - Kazemi Rashed, Fahimeh; Nourizade, Davoud; Hajebrahimi, Sakineh; Hasanzade, Kamaleddin; Otoofat, Abdolreza
Abstract : Several therapeutic options have been described for children with nocturnal enuresis, but still their efficacy and outcomes are controversial. This study compares the combined Desmopressin and Tolterodine efficacy versus Desmopressin alone efficacy in the treatment of nocturnal enuresis. One hundred children 5–16 years old with nocturnal enuresis were enrolled in a randomized trial study and were assigned to two equal groups. In a double-blind manner, we used 2 mg of Tolterodine tablet plus 20 μ g of nasal Desmopressin in group A and 20 μ g of nasal Desmopressin plus placebo in group B. The two groups were matched for age and sex ( P = 0.547, P = 0.414). The mean number of the wet nights was reduced in both groups ( P < 0.001, P < 0.001). Upon ICCS scoring in the Tolterodine + Desmopressin group, 27 (54%) had full response, 17 (34%) had partial response, and 5 (10%) had an unsuccessful outcome. In the Desmopressin + placebo group, 17 (34%) had full response, 23 (46%) had partial response, and 10 (20%) had an unsuccessful outcome. The response in the Tolterodine + Desmopressin group was significantly higher ( P = 0.049). Regarding the results, combined Tolterodine plus Desmopressin is slightly more effective than monotherapy.